2021
DOI: 10.1186/s13765-021-00639-w
|View full text |Cite|
|
Sign up to set email alerts
|

A study on catalytic and non-catalytic sites of H5N1 and H1N1 neuraminidase as the target for chalcone inhibitors

Abstract: The H1N1 pandemic in 2009 and the H5N1 outbreak in 2005 have shocked the world as millions of people were infected and hundreds of thousands died due to the infections by the influenza virus. Oseltamivir, the most common drug to block the viral life cycle by inhibiting neuraminidase (NA) enzyme, has been less effective in some resistant cases due to the virus mutation. Presently, the binding of 10 chalcone derivatives towards H5N1 and H1N1 NAs in the non-catalytic and catalytic sites was studied using molecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Berberine, lycorine, hemanthamine, aloperin, and dendrobine act as antiinfluenza agents. Similarly, in silico docking studies of compounds as anti-influenza agents were reported in the literature (Hariyono et al, 2021;Mtambo and Kumalo 2022;Abdullahi et al, 2022a, b). Table 5 represented an overview of the current study and highlights top binding affinities and majorly interacting amino acid residues.…”
Section: Resultsmentioning
confidence: 73%
“…Berberine, lycorine, hemanthamine, aloperin, and dendrobine act as antiinfluenza agents. Similarly, in silico docking studies of compounds as anti-influenza agents were reported in the literature (Hariyono et al, 2021;Mtambo and Kumalo 2022;Abdullahi et al, 2022a, b). Table 5 represented an overview of the current study and highlights top binding affinities and majorly interacting amino acid residues.…”
Section: Resultsmentioning
confidence: 73%
“…It should be noted, however, that 5 does not pass the criteria set for Pgp substrate as this compound potentially acts as a substrate for this protein. In addition, both compounds fail Caco2 permeability (<0.9) and PgpI and PgP II inhibitors criteria (Lin & Yamazaki, 2003;de Angelis and Turco, 2011;Hariyono et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…The mutagenic and toxic potency of compounds were predicted by their AMES toxicity (No), hMTD (>0.477), hERG 1 and hERG 2 inhibitor (No), ORAT and LOAEL (>2000 mg/kg, hepatotoxicity (No), skin sensitisation (No), TP toxicity (>0.5) and Minnow toxicity (>-0.3) ( Huerta E, 2007 ; Barlow et al, 2009 ; Sorell, 2016 ; McCormick, 2017 ; Gadaleta et al, 2019 ; Hariyono et al, 2021 ). From the results presented in Table 5 , both hits are likely to be potentially toxic and mutagenic, raising an alarm that the further process would need structural optimisation.…”
Section: Resultsmentioning
confidence: 99%
“…It is important to note that B14 , B29 , B31 , and B32 possess chalcone structures. Such chemical entities had been previously reported to function as anti‐influenza agents through inhibiting neuraminidase 34 . Thus, we also evaluated the inhibitory activities of these four compounds on influenza virus neuraminidase.…”
Section: Resultsmentioning
confidence: 99%
“…Such chemical entities had been previously reported to function as anti-influenza agents through inhibiting neuraminidase. 34 Thus, we also evaluated the inhibitory activities of these four compounds on influenza virus neuraminidase. As shown in Table 4, these four compounds did not exhibit any neuraminidase inhibitory activity at the maximum test concentration (100 μM), while the neuraminidase inhibitor OSC played its role as expected with an IC 50 value of 40 nM.…”
Section: Verification Of the Mechanism Of Action Of The A9 Derivativesmentioning
confidence: 99%